GAMBARAN PENGETAHUAN DAN PERILAKU IBU MENYUSUI DALAM MENINGKATKAN PRODUKSI ASI - Tia Astuti; Widia Lestari; Oswati Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Breastfeeding mothers who understand the importance of breastfeeding for their babies will try to increase or facilitate their milk production. This study aims to analyze the knowledge and behavior of breastfeeding mothers in increasing milk production in the work area of Payung Sekaki Health Center. The design of this research uses is quantitative with descriptive analytic design with a cross sectional approach. The sample in this study amounted to 90 people taken through purposive sampling method. The analysis used is univariate analysis. Respondents are in the range of early adulthood (20-35 years) as many as 54 people (60,0%) the majority of the respondents last education was tertiary education as many as 39 people (43,3 %). Most of the respondent are not working as many as 53 people (58,9%). Most of the respondents have children 1-3 people as many as 46 people (51,1%). Most of the respondents have a malay ethnity of 36 people (40,0%). Overall, 90 respondents have breastfed (100%). Some 50% respondents have good knowledge, and the majority of respondents (58.9%) have positive behavior. The results of the crosstabulation of knowledge with the behavior of breastfeeding mothers, it shows that mothers who have good knowledge of (25.6%) have negative behavior in increasing breast milk production, while mothers who have sufficient knowledge of (20.0%) have positive behavior in increasing milk production, and mothers who have sufficient knowledge less than 7.8% have negative behavior in increasing milk production. Breastfeeding mothers have good knowledge by having negative behavior in increasing breast milk production. Keywords: Knowledge, behaviour, and breastfeeding